Dissemination of knowledge: Utilization of textbooks in secondary schools in Kubang Pasu District - Mat Zin, Rasidah; Hashim, Nor Izham (2004)
For most of us, the textbook is the main weapon in our armoury and it is very difficult for most of us to teach systematically without a textbook. Like a map for a traveler in unknown territory, a textbook is a reassurance for most students. It offers a systematic revision of what they have been done, and a guide to what they are going to do (Grant, 1987). So many books these days seem to be written to help teachers in their teaching. They are the most reliable sources at teachers’ disposal. They are for teachers to use to disseminate knowledge among students in the classroom. Hence, our government has provided the textbooks in schools for so many years to meet the expectation to see our students perform well in their studies. We want the students to excel in their examinations so that they will have a bright future in this competitive world. Taking the importance of textbook in teaching and learning into consideration, one might ask, are textbooks fully utilised in schools? This paper examines the extent of the utilisation of textbooks in secondary schools in Kubang Pasu District. The questionnaire used in this study is designed basing on the combination of the William’s (1983) Evaluation Checklist, the Alan Cunningsworth’s (1984) Checklist of Evaluation Criteria and Neville Grants’ (1987) Choosing a textbook. Appropriate questions from this combination were rephrased and placed in the context of Malaysian secondary schools. A total of 314 secondary schools teachers participated in this study and it was found that even though textbooks are still used by teachers in their teaching in schools, maximum utilization is still lacking. Many claimed that the content provided in the textbooks do not live up to their expectation in terms of its suitability, practicality and relevance. A high percentage of the respondents felt that the textbooks were neither stimulating nor meeting the students’ ability. Similarly, many claimed that the content of the textbooks were not authentic and user-friendly. Consequently it is suggested that the Education Department needs to explore the real needs of students as well as the education system to develop more effective modes, dimensions and strategies for teaching and learning and use them to develop the textbooks so that they could be fully utilised.